The Application Of The Nine Elements Of Journalism In The Korean Drama H.U.S.H Episodes 11 And 12 (Semiotic Analysis Of Roland Barthes) - Annisa Dwilya Budaya (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The study deals with the application of the nine elements of journalism by Bill Kovach and Tom Rosenstiel in the Korean drama h. episode 11 and 12. The Korean drama was a series in which a journalist worked in a south Korean media; Harian Korea named, Lee Ji Soo. Lee Ji Soo was a new addition to his company that was still guided by her seniors. This series also shows the teamwork of the Harian Korea journalists in solving an issue. In the selected episode, the writer analyzed the case of the alleged firm's knife pointed at the part time worker, taken by the female lead, lee ji soo. This type of research is a qualitative descriptive using the semiotics of Roland Barthes. Hence, in this study the authors used data collection techniques by documenting, namely picking scene-scene in the Korean drama H.U.S.H (11th and 12th) episodes 11 and 12 of those containing the application of the nine elements of journalism, then a library study, which the author has obtained through journals, scripts, books, articles and so on that can support the study. The results of this research will be obtained, the Korean drama H.U.S.H, episode 11 and 12, apply seven of the nine elements journalism by Bill Kovach and Tom Rosenstiel.